Penormaan Hukum Islam dalam Sistem Hukum Indonesia Ditinjau dari Ajaran Teologi Hukum Thomas Aquinas - Dian Agung Wicaksono (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
The arrangement of Islamic law in the Indonesian legal system, which is manifested in statutory regulations, is an indication that Islamic law has become part of the Indonesian legal system. This is interesting when viewed using Thomas Aquinas' legal theology which introduces a legal dichotomy based on its sources, namely lex aeterna, lex naturalist, and lex humana. The dichotomy becomes a perspective to see at what level Islamic law is embedded in the Indonesian legal system. This research examines the existence of arrangement of Islamic law in statutory regulations from the perspective of legal theology, with research questions: (a) What is the justification for the arrangement of Islamic law substance in the Indonesian legal system? (b) How is the arrangement of the substance of Islamic law in the Indonesian legal system when viewed from the teachings of Thomas Aquinas' legal theology? This is normative legal research, by analyzing secondary data in the form of laws and libraries related to the arrangement of Islamic law and the teachings of the legal theology of Thomas Aquinas. The results indicate that the justification for the arrangement of the substance of Islamic law in the Indonesian legal system has a strong foothold because it is stated in the Pancasila